2002
DOI: 10.2169/internalmedicine.41.467
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Monitoring of Methotrexate-associated Lung Injury Using Serum Markers KL-6 and SP-D in Rheumatoid Arthritis.

Abstract: The applicability of monitoring concentrations of serum KL-6 and serum surfactant protein-D (SP-D) in the detection of methotrexate-associated lung injury (MTX pneumonitis) in patients with rheumatoid arthritis (RA) was investigated. The concentrations of these markers, sequentially measured in two patients with RA complicated with MTX pneumonitis, were increased in accordance with the severity of MTX pneumonitis. Conversely, the concentrations of these markers were decreased with the improvement of MTX pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Case studies of serum markers for drug-induced IP demonstrated that both SP-A and SP-D exhibited changes consistent with IP during the active phases of disease. The collectin markers remained elevated for a prolonged period of time (in contrast to acute-phase reactant CRP), despite improvement in the findings of diagnostic imaging, possibly indicating that inflammation of lung stroma persisted (Miyata et al, 2002;Taniguchi et al, 2005;Tanimura et al, 2006) and were thus suggested in diagnosis of IP. Among CVD patients with IP and/or fibrosis as pulmonary complication possibly with an autoimmune aetiology, there have been reported cases of systemic scleroderma (SSc), scleroderma spectrum disorders, systemic lupus erythematosus, dermatomyositis, RA, polymyositis/dermatomyositis, Sjo¨gren's syndrome, and progressive systemic sclerosis (PSS) with concurrent elevation of serum SP-A and SP-D both during active and inactive phases of disease (Takahashi et al, 1995;Maeda et al, 2001;Ihn et al, 2002;Kuwano et al, 2002).…”
Section: Collagen Vascular Diseases (Cvds)mentioning
confidence: 99%
“…Case studies of serum markers for drug-induced IP demonstrated that both SP-A and SP-D exhibited changes consistent with IP during the active phases of disease. The collectin markers remained elevated for a prolonged period of time (in contrast to acute-phase reactant CRP), despite improvement in the findings of diagnostic imaging, possibly indicating that inflammation of lung stroma persisted (Miyata et al, 2002;Taniguchi et al, 2005;Tanimura et al, 2006) and were thus suggested in diagnosis of IP. Among CVD patients with IP and/or fibrosis as pulmonary complication possibly with an autoimmune aetiology, there have been reported cases of systemic scleroderma (SSc), scleroderma spectrum disorders, systemic lupus erythematosus, dermatomyositis, RA, polymyositis/dermatomyositis, Sjo¨gren's syndrome, and progressive systemic sclerosis (PSS) with concurrent elevation of serum SP-A and SP-D both during active and inactive phases of disease (Takahashi et al, 1995;Maeda et al, 2001;Ihn et al, 2002;Kuwano et al, 2002).…”
Section: Collagen Vascular Diseases (Cvds)mentioning
confidence: 99%
“…Other factors that influence the serum SP-D level is age, gender and smoking status (Sorensen et al 2006a). Serum SP-D has proven to be a robust marker for pulmonary injury (Miyata et al 2002;Umetani et al 2002), and has thus been suggested used as a prognostic and predictive marker for a multitude of pulmonary inflammatory diseases (reviewed in Hartl and Griese 2006;Sorensen et al 2007). The antimicrobial and antiinflammatory functions of the molecule indicate that fluctuations in the molecular levels may affect the disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Mice that lack SP-D develop chronic inflammation and emphysema that can be prevented by administration of truncated recombinant human SP-D [8]. Since SP-D is synthesised predominantly within the respiratory tract, it has been evaluated as a potential biomarker in small numbers of individuals with community-acquired pneumonia [9], drug-induced lung disease [10,11], interstitial fibrosis [12] and allergic bronchopulmonary aspergillosis in cystic fibrosis [13]. Levels are reduced in bronchoalveolar lavage fluid from individuals with COPD [14], and there was a weak inverse relationship between serum SP-D level and forced expiratory volume in 1 s (FEV1) in 23 individuals with advanced COPD [15].…”
mentioning
confidence: 99%